2008
DOI: 10.1136/bmj.a1840
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of progression of arterial disease and diabetes (POPADAD) trial: factorial randomised placebo controlled trial of aspirin and antioxidants in patients with diabetes and asymptomatic peripheral arterial disease

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
500
2
19

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 846 publications
(540 citation statements)
references
References 34 publications
(28 reference statements)
6
500
2
19
Order By: Relevance
“…Nine trials reported the outcome of all-cause mortality [10,[21][22][23][24][27][28][29][30]. At a weighted mean follow up duration of 6.1 (SD = 2.9) years, the incidence of all-cause mortality was similar in both the aspirin and control groups, 7.7% (95% CI 4.3-11.1%) versus 8.5% (95% CI 4.6-12.5%) (RR = 0.93, 95% CI 0.8-1.1, P = 0.33, I 2 = 0%) (Fig 2).…”
Section: Primary Efficacy Outcomementioning
confidence: 99%
See 4 more Smart Citations
“…Nine trials reported the outcome of all-cause mortality [10,[21][22][23][24][27][28][29][30]. At a weighted mean follow up duration of 6.1 (SD = 2.9) years, the incidence of all-cause mortality was similar in both the aspirin and control groups, 7.7% (95% CI 4.3-11.1%) versus 8.5% (95% CI 4.6-12.5%) (RR = 0.93, 95% CI 0.8-1.1, P = 0.33, I 2 = 0%) (Fig 2).…”
Section: Primary Efficacy Outcomementioning
confidence: 99%
“…Three trials had multiple comparison arms and thus only the aspirin and placebo arms were included [23,25,26]. Three trials were multicenter and reported outcomes exclusively in patients without prior history of an ischemic event (including prior stroke or MI) [10,21,22], and 4 trials included low-dose aspirin ( 325mg per day) [10,21,22,24]. All of the trials included chronic stable PVD patients except one trial [25] that assessed the use of aspirin in setting of acute lower limb ischemia.…”
Section: Studies Includedmentioning
confidence: 99%
See 3 more Smart Citations